Cost of Hepatitis C care facilitation for HIV/Hepatitis C Co-infected people who use drugs. (1st March 2022) - Gutkind, Sarah; Starbird, Laura E.; Murphy, Sean M.; Teixeira, Paul A.; Gooden, Lauren K.; Matheson, Tim; Feaster, Daniel J.; Jain, Mamta K.; Masson, Carmen L.; Perlman, David C.; Del Rio, Carlos; Metsch, Lisa R.; et al.
Abstract: Background: Using data from a randomized trial, we evaluated the cost of HCV care facilitation that supports moving along the continuum of care for HIV/HCV co-infected individuals with substance use disorder. Methods: Participants were HIV patients residing in the community, initially recruited from eight US hospital sites. They received HCV care facilitation (n = 51) or treatment as usual (n = 62) for up to six months. We used micro-costing methods to evaluate costs from the healthcare sector and patient perspectives in 2017 USD. We conducted sensitivity analyses varying care facilitator caseloads and examined offsetting savings using participant self-reported healthcare utilization. Results: The average site start-up cost was $6320 (site range: $4320-$7000), primarily consisting of training. The mean weekly cost per participant was $20 (site range: $4-$30) for care facilitation visits and contacts, $360 (site range: $130- $700) for supervision and client outreach, and $70 (site range: $20-$180) for overhead. In sensitivity analyses applying a weekly caseload of 10 participants per care facilitator (versus 1–6 observed in the trial), the total mean weekly care facilitation cost from the healthcare sector perspective decreased to $110. Weekly participant time and travel costs averaged $7. There were no significant differences in other healthcare service costs between participants in the intervention and control arms. Conclusion: Weekly HCV care facilitation costs were approximately $450 per participant, but approximately $110 at a real-world setting maximum caseload of 10 participants per week. No healthcare cost offsets were identified during the trial period, although future savings might result from successful HCV treatment. Highlights: Care facilitation weekly cost was $450 per HIV/HCV co-infected trial participant. The weekly cost was lower ($110 per person) assuming a more realistic caseload. Outreach and supervision represented the largest share of care facilitation costs. No healthcare cost offsets were identified during the trial period.